Study protocol for a randomised controlled trial evaluating an evidence-based, stepped and coordinated care service model for mental disorders (RECOVER). Issue 5 (4th May 2020) - Lambert, Martin; Karow, Anne; Gallinat, Jürgen; Lüdecke, Daniel; Kraft, Vivien; Rohenkohl, Anja; Schröter, Romy; Finter, Constanze; Siem, Anna-Katharina; Tlach, Lisa; Werkle, Nathalie; Bargel, Susann; et al.
Abstract : Introduction: Healthcare systems around the world are looking for solutions to the growing problem of mental disorders. RECOVER is the synonym for an evidence-based, stepped and cross-sectoral coordinated care service model for mental disorders. RECOVER implements a cross-sectoral network with managed care, comprehensive psychological, somatic and social diagnostics, crisis resolution and a general structure of four severity levels, each with assigned evidence-based therapy models (eg, assertive community treatment) and therapies (eg, psychotherapy). The study rationale is the investigation of the effectiveness and efficiency of stepped and integrated care in comparison to standard care. Methods and analysis: The trial is conducted in accordance to the Standard Protocol Items: Recommendations for Interventional Trials Statement. The study aims to compare the RECOVER model with treatment as usual (TAU). The following questions are examined: Does RECOVER reduce healthcare costs compared with TAU? Does RECOVER improve patient-relevant outcomes? Is RECOVER cost-effective compared with TAU? A total sample of 890 patients with mental disorders will be assessed at baseline and individually randomised into RECOVER or TAU. Follow-up assessments are conducted after 6 and 12 months. As primary outcomes, cost reduction, improvement in symptoms, daily functioning and quality of life as well as cost-effectiveness ratios will be measured. In addition, several secondary outcomes will be assessed. Primary and secondary outcomes are evaluated according to the intention-to-treat principle. Mixed linear or logistic regression models are used with the direct maximum likelihood estimation procedure which results in unbiassed estimators under the missing-at-random assumption. Costs due to healthcare utilisation and productivity losses are evaluated using difference-in-difference regressions. Ethics and dissemination: Ethical approval from the ethics committee of the Hamburg Medical Association has been obtained (PV5672). The results will be disseminated to service users and their families via the media, to healthcare professionals via professional training and meetings and to researchers via conferences and publications. Trial registration number and registry name: ClinicalTrials.gov (NCT03459664 ), RECOVER Protocol version: 19 March 2020 (V.3.0)